2014
DOI: 10.1117/12.2056741
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary design for the GMT-Consortium Large Earth Finder (G-CLEF)

Abstract: The GMT-Consortium

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 14 publications
0
15
0
Order By: Relevance
“…narrow-band photometry such as the Pristine photometric survey (Starkenburg et al 2017). For Boötes I and Hercules, the two most massive satellites targeted in Pristine, we estimate an average number of Pop III red giant branch stars to be about 0.3.…”
Section: Satellite Properties and Implications For Observationsmentioning
confidence: 97%
“…narrow-band photometry such as the Pristine photometric survey (Starkenburg et al 2017). For Boötes I and Hercules, the two most massive satellites targeted in Pristine, we estimate an average number of Pop III red giant branch stars to be about 0.3.…”
Section: Satellite Properties and Implications For Observationsmentioning
confidence: 97%
“…Avoiding or mitigating these effects would require using new types of detectors which are not prone to these problems and/or new approaches to reducing echelle spectra. These problems may be addressed on the longer timescales involved in preparing for and building G-Clef on the Giant Magellan Telescope (GMT) (Szentgyorgyi et al 2014) and HIRES on the European Extremely Large Telescope (E-ELT) (Zerbi et al 2014). These telescopes will have much higher light collecting area which will enable significant improvements in S/N ratio and, therefore, statistical uncertainties in ∆α/α measurements.…”
Section: Next-generation Spectrographs and Telescopes: Expected Systementioning
confidence: 99%
“…Atmospheric dispersion compensation (ADC) is integral to this relay system. These optics have been described in an earlier publication 1 .…”
Section: Spectrograph Thermal Enclosurementioning
confidence: 99%
“…Modeling has shown that the GMT adaptive optics system can improve both the near-field stability within the spectrograph and throughput, in some cases by a factor of 2 1 . A provision exists to upgrade the GCFEA to accommodate a wavefront sensor when adaptive optics are implemented on the GMT some time after first light 23 .…”
Section: Spectrograph Thermal Enclosurementioning
confidence: 99%
See 1 more Smart Citation